2019
DOI: 10.1096/fj.201802727r
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation and a non–24‐h working schedule lead to extensive alterations in physiology and behavior

Abstract: Most organisms on Earth possess circadian rhythms in their physiology and behaviors that allow them to resonate with the cycling environment over a 24‐h period. However, in human society, a substantial quantity of jobs requires non–24‐h working and rest or shift schedules, which causes more or less misalignment in circadian rhythms and disorders as a consequence. In this work, we conducted a sleep deprivation (SD) and non–24‐h working and rest schedule (8 h on and 4 h off) experiment over 10 d in total and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…A survey of 122 submarine crew members indicated that over 77% of them had medical complaints, and most complaints were about sleeping difficulty [ 68 ]. However, prevalent studies have demonstrated that under non-24-h conditions, both the quantity and quality of sleep are altered [ 67 , 69 , 70 ]. In real missions, the sleep time of the submarine crew varies in a wide range, extending from 5.75 h to 9 h, which may be influenced by many environmental factors [ 60 ].…”
Section: Effects Of Non-24-h Conditions On Human Health and Performanmentioning
confidence: 99%
See 3 more Smart Citations
“…A survey of 122 submarine crew members indicated that over 77% of them had medical complaints, and most complaints were about sleeping difficulty [ 68 ]. However, prevalent studies have demonstrated that under non-24-h conditions, both the quantity and quality of sleep are altered [ 67 , 69 , 70 ]. In real missions, the sleep time of the submarine crew varies in a wide range, extending from 5.75 h to 9 h, which may be influenced by many environmental factors [ 60 ].…”
Section: Effects Of Non-24-h Conditions On Human Health and Performanmentioning
confidence: 99%
“…The level of insulin is under the control of the circadian clock, which peaks at night in humans [ 78 ]. Ma et al [ 70 ] found that saliva insulin dramatically increased late at night and early in the morning in subjects under a schedule of 8 h for work and rest and 4 h for sleep. Consistently, the insulin levels and insulin: glucose ratios were increased in mice under LD 10 conditions [ 81 ].…”
Section: Effects Of Non-24-h Conditions On Human Health and Performanmentioning
confidence: 99%
See 2 more Smart Citations
“…Although numerous medical and ergonomical problems have been reported, rotating shift work schedules are still commonly employed in industrial society including maritime tasks and the detrimental effects have not been su ciently concerned. For instance, non-24 h and frequently rotating schedules are commonly used in maritime missions [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%